Uso potencial de aceites esenciales como una alternativa de control contra Bactericera cockerelli - Macas Medina, Santiago David (2023)
The psyllid Bactericera cockerelli (Šulc) (Hemiptera: Triozidae) is a pest of the tomato crop Solanum lycopersicum which causes direct damage by feeding on the phloem of the plant. To control and minimise the damage caused by this insect pest, synthetic insecticides are used, which can be hazardous to non-target organisms. However, essential plant oils and their active compounds are recognised as sustainable tools for pest management. Here, the chemical composition of the essential oil of Ruta graveolens and Ocotea quixos was extracted and evaluated, and their activities against Bactericera cockerelli were assessed. Chromatographic analysis revealed that 2-Nonanone (42.23 %), 2-Undecanone (39.91 %), are the main compounds from R. graveolens and (E)-Cinnamyl acetate (16.59 %), trans-Caryophyllene (10.47 %) and 1,8-Cineole (8.21 %) from O. quixos. The essential oil of R. graveolens was not repellent to adults of B. cockerelli when it was exposed for 24 hours. Similarly, the essential oil of O. quixos failed to repel the psyllid, except at the LC75 concentration 0.051 µl/cm2 (IR = 0.77) which showed significant difference when compared to the control. The essential oils of R. graveolens LC50 = 0.131 (0.123-0.139) µl/cm2 and O. quixos LC50 = 0.131 (0.123-0.139) µl/cm2 were toxic to adults of B. cockerelli. Overall, this study demonstrates that these essential oils could be successfully integrated into management programmes against B. cockerelli. Key words: Biomolecule, Toxicity, Repellency, Tomato psyllid.